Information-documentation didactic and inclusion, a research-intervention using combined methods - Frisch, Muriel (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
The research intervention “Information-Documentation and inclusion” reported in this article falls within the context of the new primary and lower secondary school curriculum in France that are promoting inclusive schools as a better alternative for students with disabilities. It regarding a group of vocational high schools and college female professor-documentalists, benefiting in their respective institutions from Localized Units for Inclusive School (LUIS). Professorsdocumentalists are thus involved in the evolution of their professional practices, and in what we have called forms of “reflexive thinking effectiveness”. We are presenting the original mechanism of research-intervention and the combined methods we used. They lead us on to a characterization of seven types of “didactic interaction”.